Hydrogel-chitosan and polylactic acid-polycaprolactone bioengineered scaffolds for reconstruction of mandibular defects: a preclinical in vivo study with assessment of translationally relevant aspects - Ferrari, Marco; Taboni, Stefano; Chan, Harley H. L.; Townson, Jason; Gualtieri, Tommaso; Franz, Leonardo; Ruaro, Alessandra; Mathews, Smitha; Daly, Michael J.; Douglas, Catriona M.; Eu, Donovan; Sahovaler, Axel; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Reconstruction of mandibular bone defects is a surgical challenge, and microvascular reconstruction is the current gold standard. The field of tissue bioengineering has been providing an increasing number of alternative strategies for bone reconstruction. Methods: In this preclinical study, the performance of two bioengineered scaffolds, a hydrogel made of polyethylene glycol-chitosan (HyCh) and a hybrid core-shell combination of poly (L-lactic acid)/poly (ε-caprolactone) and HyCh (PLA-PCL-HyCh), seeded with different concentrations of human mesenchymal stromal cells (hMSCs), has been explored in non-critical size mandibular defects in a rabbit model. The bone regenerative properties of the bioengineered scaffolds were analyzed by in vivo radiological examinations and ex vivo radiological, histomorphological, and immunohistochemical analyses. Results: The relative density increase (RDI) was significantly more pronounced in defects where a scaffold was placed, particularly if seeded with hMSCs. The immunohistochemical profile showed significantly higher expression of both VEGF-A and osteopontin in defects reconstructed with scaffolds. Native microarchitectural characteristics were not demonstrated in any experimental group. Conclusion: Herein, we demonstrate that bone regeneration can be boosted by scaffold- and seeded scaffold-reconstruction, achieving, respectively, 50% and 70% restoration of presurgical bone density in 120 days, compared to 40% restoration seen in spontaneous regeneration. Although optimization of the regenerative performance is needed, these results will help to establish a baseline reference for future experiments.